Effect of ketogenic diet on alzheimer's disease to improve cognitive function: A literature review - Anjani Daniyil Khoiroh (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Alzheimer's is the most common cause of neurodegenerative dementia which is characterized by reduced cognitive function. Alzheimer's disease is a serious global problem because so far no effective treatment has been found to prevent it. Improving diet can be used as therapy to prevent cognitive decline. The ketogenic diet is one of the recommended therapies because it is neuroprotective.Purpose: To review several studies related to the effect of giving a ketogenic diet in improving cognitive function in people with Alzheimer's.Method: This study used the literature review method using the PRISMA protocol. Literature searches were conducted online, sourced from Scopus, Science Direct, PubMed, ProQuest, and SpringerLink databases by entering a number of relevant keywords. The key words are